Concurrent Kimura disease and lupus nephritis: A case report. Issue 41 (October 2016) - Wang, Haitao; Fang, Fang; Sun, Ying; Wang, Songlan; Mao, Yonghui
Abstract: Background: Kimura disease is a rare chronic inflammatory disorder with peripheral eosinophilia and elevated serum IgE and is also frequently complicated by nephropathy. Methods: We report a rare case of Kimura disease concomitant with lupus nephritis in a 72-year old male patient with recurrent unexplained lymphadenopathy, renal lesions, and immunologic abnormalities. Results: The patient was successfully managed with gamma immunoglobulin, intravenous pulse methylprednisolone therapy, hydroxychloroquine, and prednisone. Conclusion: This is the first report of a case of Kimura disease concomitant with lupus nephritis and highlights the importance of considering lupus nephritis as a possible concurrent disease in patients with Kimura disease that have immunologic abnormalities.